2012
DOI: 10.1007/s12010-012-9592-0
|View full text |Cite
|
Sign up to set email alerts
|

Sago Pith Residue as an Alternative Cheap Substrate for Fermentable Sugars Production

Abstract: Sago pith residue is one of the most abundant lignocellulosic biomass which can serve as an alternative cheap substrate for fermentable sugars production. This residue is the fibrous waste left behind after the starch extraction process and contains significant amounts of starch (58%), cellulose (23%), hemicellulose (9.2%) and lignin (3.9%). The conversion of sago pith residue into fermentable sugars is commonly performed using cellulolytic enzymes or known as cellulases. In this study, crude cellulases were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
4
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 22 publications
3
31
4
5
Order By: Relevance
“…Sago pith flour, as a part of the dry extraction production, contains a high amount of starch (86%), while, as a by-product from the inefficient wet extraction process, sago hampas contains approximately 55% starch and 15% fiber on a dry weight basis. Composition of this sago hampas was similar to that reported by Lingga et al (2012) which showed 58% starch, compared to Awg-Adeni et al (2013) who reported a lower starch content (30-45%) and higher fiber content (30-35%).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Sago pith flour, as a part of the dry extraction production, contains a high amount of starch (86%), while, as a by-product from the inefficient wet extraction process, sago hampas contains approximately 55% starch and 15% fiber on a dry weight basis. Composition of this sago hampas was similar to that reported by Lingga et al (2012) which showed 58% starch, compared to Awg-Adeni et al (2013) who reported a lower starch content (30-45%) and higher fiber content (30-35%).…”
Section: Introductionsupporting
confidence: 84%
“…Hampas also contains high amounts of cellulose (11%), hemicellulose (7.6%), and lignin (12%) (Utami et al 2014); Abd-Aziz (Lingga et al 2012), a source for biohydrogen production (Jenol et al 2014), and a composite material for biofoam production (Lai et al 2013;Utami et al 2014;Rao and Kumar 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When used on a dry basis, sago hampas contains 58 % starch, 23 % cellulose, 9.2 % hemicellulose and 4 % lignin [28]. Sago hampas is the starchy lignocellulosic by-product from the pith of Metroxylon sagu (sago palm) following the starch extraction process [26].…”
Section: Untreated Adsorbentmentioning
confidence: 99%
“…According to Abd-Aziz (2002), the composition of sago pith waste on a dry weight basis contains 65.7% starch, 14.8% crude fiber, 1% crude protein, 4.1% ash, and 59.1% moisture. Linggang et al (2012) reported that sago pith waste contains 58% starch, 23% cellulose, 9.2% hemicellulose, and 4% lignin on a dry basis. Awg- Adeni et al (2013) state that on a dry basis, the proportions of sago pith waste consist of 30-45% starch, 5-7% ash, 1% protein, and 4.6-4.7% fiber.…”
Section: Problems Of Sago Starch Extractionmentioning
confidence: 99%